Your next move : the leader's guide to navigating major career transitions - Watkins, Michael, 1956- (Boston, Massachusetts : Harvard Business Press, 2009)
"Whether you're going for that promotion, looking to jump ship, or change careers entirely, Michael Watkins' Your Next Move is a book you'll want to read." So starts the positive review of Your Next Move on the influential 800 CEO Read website. It's true that all leaders--no matter how seasoned--need guidance through the professional changes that define a career. In fact, transitions into new roles are the crucibles in which leaders get their toughest tests, and they're the defining factor in professional careers today. Yet far too often, leaders fail to transition effectively into new roles. The resulting costs are high, for individual careers and for organizations. In Your Next Move, leadership-transition guru Watkins shows how you can survive and thrive in all the major transitions you will face during your career-including promotions, leading former peers, on-boarding into a new organization, making an international move, or turning around or realigning an organization. With real-life examples and case studies, Watkins illustrates the defining hurdles associated with each type of transition. He then provides the insights, strategies, and tools you'll need to accelerate through these crucial turning points and continue moving up in your career. The necessary complement to the author's bestselling guide The First 90 Days, which has been translated in more than 20 languages worldwide, Your Next Move offers the keen observations, tried-and-true management wisdom, and practical good sense Watkins is renowned for. It's a vital resource for any manager or executive seeking to maintain career momentum. To quote the reviewer from above: "It's not just about "moving" but about what happens when those actions are taken. Success or failure are the two options, and which option you emerge with will determine what happens going forward. Watkins' book definitely has the research and insight to equip you for the better of the two paths."
Intro; Contents; Acknowledgments; Introduction: Your Next Move; Chapter 1: The Promotion Challenge; Chapter 2: The Leading-Former-Peers Challenge; Chapter 3: The Corporate Diplomacy Challenge; Chapter 4: The Onboarding Challenge; Chapter 5: The International Move Challenge; Chapter 6: The Turnaround Challenge; Chapter 7: The Realignment Challenge; Chapter 8: The STARS Portfolio Challenge; Conclusion: Designing Companywide Transition-Accereration Systems; Notes; Index; About the Author.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 22, 2021).
Master record variable field(s) change: 050, 082
Keywords: Executives; Career development; Promotions; Leadership; Management; Administrative Personell; Leadership; Personell Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Reference; BUSINESS & ECONOMICS -- Skills; Career development; Executives; Leadership; Management; Promotions; elektronické knihy; electronic books